CIRCULATING SERUM ADIPONECTIN AND OXIDATIVE STRESS BIOMARKERS IN PREDIABETES AND TYPE 2 DIABETES MELLITUS PATIENTS - RACHNA SHARMA; SATYANARAYANA P; PALLAVI ANAND; SHRAWAN KUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: Adipocytokines and oxidative stress have been independently studied in various morbidities, but their interrelationship in mediating insulin resistance and type 2 diabetes mellitus is still unclear. Thus, the present study was aimed at evaluating malondialdehyde (MDA) levels in pre-diabetes and diabetics and correlating it with adiponectin levels. Methods: Fifty controls, 50 pre-diabetic, and 50 diabetic patients were enrolled. Plasma MDA, uric acid, and adiponectin were measured in the blood samples. Serum MDA adiponectin was analyzed by enzyme-linked immunosorbent assay and uric acid was analyzed by uricase method. Results: Pre-diabetic and diabetic patients had higher levels of MDA and uric acid, while the level of adiponectin was low compared to controls. Correlation of MDA was positive with uric acid but negative with adiponectin in diabetic patients. Likewise, adiponectin and uric acid were also correlated negatively. In pre-diabetes, adiponectin was significantly and negatively correlated with MDA and uric acid. Conclusions: Pre-diabetic and diabetic patients have increased oxidative stress, which is also linked with adipokine abnormalities. From this study, we observed that oxidative stress suppresses adiponectin production which is the protective adipokine in hyperglycemia. Thus, oxidative stress may serve as an indicator or target for in the control of hyperglycemic stress.